2020
DOI: 10.1097/shk.0000000000001558
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NF-κB1 and the Non-canonical NF-κB Signaling Pathway in the Pathogenesis of Acute Kidney Injury in Shiga-toxin-2-induced Hemolytic-uremic Syndrome in Mice

Abstract: The hemolytic-uremic syndrome (HUS) is a thrombotic microangiopathy which can occur as a severe systemic complication after an infection with Shiga-toxin-(Stx)-producing Escherichia coli (STEC). Elevated levels of proinflammatory cytokines associated with the classical nuclear factor kappa-light-chain-enhancer of activated Bcells (NF-kB) signaling pathway were detected in the urine of HUS patients. Thus, we hypothesize that the immune response of the infected organism triggered by Stx can affect the kidneys an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…In AKI with sterile inflammation, B cells produce CCL7 to recruit neutrophils and monocytes to the injured kidney ( Inaba et al, 2020 ). In our analysis, CCL5 , CCL19 , CCL21 , CXCR5 , and CXCL2 were upregulated in AKI, which was consistent with that reported in previous studies ( Sanz et al, 2010 ; Winterberg et al, 2013 ; Wohlfahrtova et al, 2015 ; Sobbe et al, 2020 ). Moreover, Hedgehog signaling was reported to be upregulated and protected tubular cells in various AKI models, such as ischemia/reperfusion ( Zhuo et al, 2019 ) and obstructive kidney injury ( Rauhauser et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…In AKI with sterile inflammation, B cells produce CCL7 to recruit neutrophils and monocytes to the injured kidney ( Inaba et al, 2020 ). In our analysis, CCL5 , CCL19 , CCL21 , CXCR5 , and CXCL2 were upregulated in AKI, which was consistent with that reported in previous studies ( Sanz et al, 2010 ; Winterberg et al, 2013 ; Wohlfahrtova et al, 2015 ; Sobbe et al, 2020 ). Moreover, Hedgehog signaling was reported to be upregulated and protected tubular cells in various AKI models, such as ischemia/reperfusion ( Zhuo et al, 2019 ) and obstructive kidney injury ( Rauhauser et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Sobbe et al [61] showed that both the classical (RelA-p50) and alternative (RelB-p52) NF-κB pathways were active in Stx-injected mice detecting upregulation of RelA-target cytokines CCL20, CXCL1 and CXCL10 that were also differentially expressed in our dataset (Figure 5L).…”
Section: Activity (V) Particular Gene Transcription Leading To Cytokine Secretionmentioning
confidence: 68%
“…Sobbe et al . [60] showed that both the classical (RelA-p50) and alternative (RelB-p52) NF-κB pathways were active in Stx-injected mice detecting upregulation of RelA-target cytokines CCL20, CXCL1 and CXCL10 that were also differentially expressed in our d ataset (figure 5L).…”
Section: Discussionmentioning
confidence: 91%